Pengelolaan Perbenihan Nilam Untuk Mencegah Penyebaran Penyakit Budok (Synchytrium pogostemonis) - WAHYUNO, WAHYUNO (Perspektif, 2010)
ABSTRAKTanaman nilam (Pogostemon cablin) adalah tanaman penghasil minyak patchouli yang banyak diperlukan dalam industri parfum. Indonesia merupakan negara penghasil minyak nilam terbesar di dunia.  Tanaman nilam telah tersebar luas di 12 propinsi di Indonesia, dengan  penghasil  utama  propinsi  Nanggroe  Aceh Darusalam, Sumatera Utara, Sumatera Barat, Bengkulu, Jawa Barat dan Jawa Tengah. Tanaman nilam bukan tanaman asli Indonesia, jarang membentuk bunga, dan keragaman genetik yang ada di Indonesia sempit.  Perbanyakan secara vegetatif dengan menggunakan setek pucuk atau setek batang merupakan cara perbanyakan nilam yang utama di Indonesia.  Kekeringan dan gangguan OPT merupakan kendala  yang  banyak  dijumpai  di  sentra  produksi nilam. Akhir-akhir ini penyakit budok yang disebabkan oleh cendawan Synchytrium pogostemonis banyak ditemukan di sentra produksi  nilam di Indonesia. Usaha untuk mengembangkan teknologi pengendalian terhadap S. pogostemonis sedang dilakukan dalam dua tahun terakhir ini. Karakteristik S.  pogostemonis  yang  mempunyai  struktur  bertahan yang kuat dan mudah tersebar melalui benih nilam menjadi perhatian dalam usaha menekan kehilangan hasil  akibat  serangan  S. pogostemonis. Pengelolaan perbenihan yang tepat merupakan cara yang paling efektif untuk menekan penyebaran S. pogostemonis  dan pencemaran  ke  daerah  penanaman  nilam  lainnya, diikuti dengan sertifikasi perbenihan dan pemantauan lalulintas benih.Kata kunci: Penyakit budok, Pogostemon cablin,Synchytrium pogostemonis, perbenihan, penyebaran ABSTRACTNursery Management of Patchouli for Inhibit Synchytrium pogostemonis DistributionPatchouli (Pogostemon cablin) is important patchouli oil producing  plant  that  mostly  needed  for  parfume industries. Indonesia is the bigest patcholi oil producing country. The plant is widely cultivated in Indonesia over 12 provincies, with the main producer areas  mainly  in  Nanggroe  Aceh  Darusalam,  North Sumatera, West Sumatera, Bengkulu, West Java and Central Java.  The patchouli is not Indonesia origin, and sexual reproduction structure is rarely formed in Indonesia.   Therefore   the   genetic   diversity   of   the patchouli in Indonesia is narrow. Young vein cutting and  stem  cutting  are  common  mass  propagation method for this plant in Indonesia. Drought and the occurennce of insect pests and diseases are the main constraint   in   patchouli   cultivation   in   Indonesia. Recently,   a   disease   namely   budok   caused   by Synchytrium  pogostemonis  an  obligate  plant  parasite fungus  is  reported  widely  distributed  in  patchouli cultivation centre areas in Indonesia. Attempts to find effective control measures of the disease has just been conducted in the last two years. Thus only limited informations on the fungus has been obtained up to present. The fungus has winter spore state that leads the fungus organ persist in the soil, and still viable for a long period. The existence of the winter spore should be  main  focus  in  reducing  yield  lost  due  to  S. pogostemonis infection. Proper in seedling preparation and handling are considered the best way to inhibit S. pogostemonis  distribution  and  contaminating  budok disease   free   areas.   Improvement   in   pogostemon seedling   preparation   procedure,   and   statutory   in seedlings transportation are considered the best way to delimit of budok disease impact in the present time; then  followed  by  seedling  certification,  and  stricly quarantine monitoring also supose to be intensively carried out immediately.Keywords:  Wart  disease,  Pogostemon  cablin,  Synchy-trium pogostemonis, nursery, spreading